Budd-Chiari syndrome in a young patient with celiac sprue: A case report - Ahmet DANALIOĞLU; Şule POTUROĞLU; Mine GÜLLÜOĞLU; Kadir DEMİR; Fatih BEŞIŞIK; Yılmaz ÇAKALOĞLU; Uğur ÇEVİKBAŞ; Atilla ÖKTEN (Turkish Journal of Gastroenterology, 2019)
-